The effect of protein level and added amino acids in sorghum grain-soybean meal rations for swine - Koch, B.A.; Howard, R.D.; Kropf, Donald H.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
More information is needed on the optimum level of protein in sorghum grain-soybean meal rations for swine. Theoretically the protein value of a swine ration should be improved if the most limiting amino acids are added. This experiment was conducted to determine the most favorable level of protein in sorghum grain-soybean meal rations and the effect of added lysine and methionine.
Swine Industry Day 1968 is known as Swine Day, 1968
Keywords: Swine; Sorghum; Protein; Amino acid; Methionine